L10 Stacked Binaries as Candidates for Hard‐Magnets: FePt, MnAl and MnGa. Issue 8 (4th July 2017) - Matsushita, Yu‐ichiro; Madjarova, Galia; Flores‐Livas, José A.; Dewhurst, J. K.; Felser, C.; Sharma, S.; Gross, E. K. U.
Abstract : The authors present a novel approach for designing hard magnets including no rare‐earth and less expensive elements, based on the computational quantum mechanics. They formed stacks from different binaries, i.e., L10 ‐FePt, MnGa, and MnAl, and search for optimal composition making new structures potentially interesting candidates for permanent magnets. The authors also studied stoichiometrically identical arrangements as quaternary (un)distorted Heusler structures. Abstract : We present a novel approach for designing new hard magnets by forming stacks of existing binary magnets to enhance the magneto crystalline anisotropy. This is followed by an attempt at reducing the amount of expensive metal in these stacks by replacing it with cheaper metal with similar ionic radius. This strategy is explored using examples of FePt, MnAl and MnGa. In this study a few promising materials are suggested as good candidates for hard magnets: stacked binary FePt2 MnGa2 in structure where each magnetic layer is separated by two non‐magnetic layers, FePtMnGa and FePtMnAl in hexagonally distorted Heusler structures and FePt0.5 Ti0.5 MnAl.